Unsur Pidana Terhadap Aksi Penarikan Motor oleh Debt Collector (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
In the development of massive activities, transportation is needed to carry out mobility so as to facilitate each individual in carrying out his daily work and activities. The vehicle used by most people is a motorized vehicle, this vehicle is a vehicle that is used and obtained by purchasing it through cash or credit. In the case of buying on credit itself, there are many problems, namely the debtor who pays the installments is not necessarily smooth in making payments, this certainly creates losses for the creditor who provides the motorbike on credit. In an effort to minimize these losses and risks, the creditor cooperates and hires a third party, namely a debt collector to collect or withdraw the motor vehicle that is the object of the pre-credit agreement, now this research discusses the problems that arise in the community regarding withdrawal by debt collectors whether this action has criminal elements or not.